The −3279C>A and −924A>G polymorphisms in the FOXP3 Gene Are Associated With Viral Load and Liver Enzyme Levels in Patients With Chronic Viral Liver Diseases - Pereira, Leonn M. S.; Amoras, Ednelza da Silva Graça; da Silva Conde, Simone R. S.; Demachki, Sâmia; Monteiro, Jaqueline C.; Martins-Feitosa, Rosimar N.; da Silva, Andrea N. M. R.; Ishak, Ricardo; Vallinoto, Antonio C. R. (Frontiers in Immunology, 2018)
The transcription factor FOXP3 is an essential marker of the development and activation of regulatory T cells (Tregs), which are cells specialized in the regulation and normal tolerance of the immune response. In the context of chronic viral liver diseases, Tregs participate in the maintenance of infections by promoting histopathological control and favor the immune escape of viral agents by suppressing the antiviral response. Single nucleotide polymorphisms (SNPs) may influence the function of FOXP3 in a number of pathological conditions. The present study sought to evaluate the influence of SNPs in the FOXP3 gene promoter region in patients with chronic viral liver diseases. Three SNPs (-3279C>A, -2383C>T and -924A>G) were analyzed in groups of patients with chronic hepatitis C (CHC), active chronic hepatitis B (CHB-A), inactive chronic hepatitis B (CHB-I) and a healthy control group (CG) using real-time PCR. The frequencies of the polymorphic variants were compared between groups and correlated with liver histopathological characteristics and enzyme levels (i.e., alanine aminotransferase (ALT), aspartate aminotransferase (AST) and gamma-glutamyl transpeptidase (GGT)) obtained via biopsy and from the clinical records of the participating patients, respectively. For the -2338C>T SNP, no significant differences were found in the frequencies of variants between groups or in the histological findings. Significant associations between the polymorphisms and the CHB-I group were not established. The -3279C>A SNP was associated with altered viral loads (log10) and GGT levels in CHC patients with advanced stages of inflammatory activity and liver fibrosis. The -924A>G SNP was associated with altered viral loads (log10) and liver enzyme levels among CHB-A patients with milder inflammation and fibrosis. However, the frequencies of the -3279C>A and -924A>G polymorphisms were not directly associated with the histopathological profiles of the analyzed patients. These polymorphic variants may influence hepatic function in patients with chronic viral liver diseases but are not directly associated with the establishment of the degree of inflammatory activity and liver fibrosis